Organizational Communication Style of Village Head in Improving Public Services to the Community in Sikunang Village Wonosobo Central Java - Pradhana, Yudha; Kadarsih, Dinar (Communicare : Journal of Communication Studies, 2025)
Communication plays a crucial role in human life, serving as a medium for conveying messages and information. It is utilized in various settings, including within families, communities, and organizations. In organizations, whether corporate or governmental, communication is vital for achieving objectives and ensuring smooth operations. In rural governance, the village head serves as the leader responsible for providing public services to the community in accordance with their formal duties and functions. This study aims to examine and analyze the organizational communication strategies employed by the Sikunang Village Government in Wonosobo Regency, Central Java, in improving public services. The research utilizes a descriptive qualitative approach, gathering data through direct interviews and observations of the village government. The findings highlight the significance of effective organizational communication in enhancing public service delivery and demonstrate how the leadership style of the village head influences group communication within the local government.